Liability of Mining Companies Related to Environmental Pollution in the Perspective of Prophetic Law: Pertanggungjawaban Perusahaan Tambang Terkait Pencemaran Lingkungan dalam Perspektif Hukum Profetik - Suciati, St. Muslimah; Sarif, Asri; Rasmuddin; Arfa, Arfa (Rechtsidee, 2022)
This study aims to analyze aspects of mining company liability related to environmental pollution in the perspective of prophetic law. A review of prophetic law is used as an analytical knife to confirm the existence of prophetic law, one of which emphasizes "unity" between the interests of humans and the universe (including the environment). This research is a normative legal research by prioritizing the concept and statutory approach. The results of the study confirm that proper legal responsibility for mining companies if it is proven that there is environmental pollution in a preventive manner or prevention, mining companies need to anticipate that before mining companies carry out mining activities, they must submit a post-mining reclamation plan and provide a post-mining reclamation guarantee fund. Then in the implementation of mining activities supervision must be carried out continuously and negotiate/persuade or supervise so that mining companies carry out their mining activities in compliance with permit conditions and other conditions for carrying out environmentally sound mining activities. Viewed from the perspective of prophetic law, legal accountability for mining companies in relation to environmental pollution is actually in accordance with three aspects of prophetic law, namely aspects of transcendence, humanization, and liberation. Therefore, in order to make law enforcement effective regarding legal liability for mining companies in relation to environmental pollution, it is necessary to harmonize and synchronize laws and regulations as well as the need for efforts to maintain coherence between statutory regulations and practice in the field.